Feminist Metatheatricalism: Escofet's Ritos del corazón - Zatlin, Phyllis (Latin American Theatre Review, 2001)
The protagonist of Cristina Escofet’s Ritos del corazón is a writer who cannot escape the feminine myths of the past, among them, her own youthful self. The action takes place in a theatre, where historical characters, in search of an audience, come to act out their roles. Featuring an all-female cast, Ritos del corazón evokes "personajes de la realidad eterna" ranging from women of earlier centuries, to icons of twentieth-century popular culture, to members of Laura’s own family, including her mother as a ten-year old who does not want to get married and have children. Through its metatheatrical and comic strategies, the play effectively deconstructs gender roles, revealing their performativity. (PZ)